Factors influencing the content of Smart City initiatives(particularly based on institutional theories of organization) - Karina RADCHENKO (Smart Cities and Regional Development Journal)
Objectives This paper aims to consider the factors shaping the smart city structures from the perspective of institutional organizational theories and in context of sustainable development. Prior work The previous findings have revealed significant lack of attention to factors impacting the smart city concept. Approach The paper applies literature reviews and survey analysis involving the experts in the field of smart cities. Results The paper applies literature reviews and survey analysis involving the experts in the field of smart cities. Implications The study provides the perspective useful for local and regional authorities as well as other parties involved in smart city implementation and development. Value The paper proposes the extended multi-factor smart city model approach encompassing the factors from different theories.